Effect of Bleaching Containing Polydopamine and Chitosan-Modified TiO2 on the Level of Brightness and Microhardness of Teeth - Rohmawati, Lydia; Alfina, Fitria Tahta; Pratiwi, Devi Ragita Putri; Pratama, Angela Arin; Muadhif, Fariz Irkham; Setyarsih, Woro; Munasir, Munasir; Nerito, Prima; Darminto, Darminto (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2024)
Teeth bleaching techniques generally use high concentrations of bleaching agents such as H2O2, which can harm dental health. Therefore, an alternative method is needed to minimize the use of H2O2. The aim of this study was to determine the characteristics and effectiveness of a teeth-whitening gel made from polydopamine and chitosan-modified TiO2. The research phase began with the extraction of TiO2 from Tulungagung sand using the leaching method, and then the TiO2 was modified with polydopamine and chitosan. XRD, FTIR, and TEM were used to characterize the fabrication results. The results of XRD analysis showed that the diffraction peaks of polydopamine and chitosan-modified TiO2 had the characteristics of anatase phase TiO2. Functional groups of polydopamine and chitosan-modified TiO2 were identified from the results of FTIR analysis. The TEM image showed the spherical shape with a core-shell structure, where the TiO2 particles were covered with polydopamine and chitosan. The addition of H2O2 at 3% to the polydopamine and chitosan-modified TiO2 gel transformed it into a tooth whitening agent. After that, the teeth without soaking and those soaked in cola were bleached with the whitening gel using visible light irradiation three times for 15 min each time. The bleaching results showed that the 0.25-g polydopamine-modified TiO2 formula whitening gel effectively whitened teeth without causing a significant change in the microhardness value of the tooth surfaces, even at low concentrations of H2O2